Simulating the impact of check dams on river flow-a case study in Bharathappuzha river basin - ARSHANA V.K HARITHA A HREDHYA HARIDAS JYOTHISH V RASHIDA RAJUVA T.A; Dr. K.K Sathian (Guide) (Tavanur 2010 Department of Land and Water Resources and Conservation Engineering)
Simulating the impact of check dams on river flow-a case study in Bharathappuzha river basin
Simulating the impact of check dams on river flow-a case study in Bharathappuzha river basin